Peran Non-Tuberkulosis Mikobakterium dalam Infeksi Ekstra Paru: A Systematic Review - Laila Larissa, Luna; Quazwain, Fairuz; Hanina (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Extrapulmonary tuberculosis (TBEP) is a diagnostic challenge with significant morbidity and mortality. This study aimed to identify non-tuberculous mycobacterium (NTM) types in extra-pulmonary infections through a systematic review using PRISMA guidelines. A literature search was conducted on Google Scholar, PubMed, and Science Direct with specific keywords, resulting in 222 studies identified, with 15 studies meeting the inclusion criteria. Results showed Mycobacterium avium and M. kansasii as the most prevalent NTM species in extra-pulmonary infections. Study limitations included methodological heterogeneity and variation in operational definitions between studies.